The Use of Project Based Learning (PBL) with Canva to Increase Students’ Activity - Niladatika, Niladatika; Nur, Rafiah; Ammade, Salasiah (STAIN Majene, 2023)
This study aimed to increase students’ activities in face-to-face learning through project-based learning with Canva. This research was one pre-experimental. The research subjects were students of SMAN 11 Pinrang class X MIPA 3, totaling 32 students. The data were collected using observation checklist tests with 5 indicators they are visual activities, oral activities, listening activities, writing activities and mental activities. The researcher was helped by four observers in observing students’ activities in three meetings. The data was then analyzed descriptively. The result of this study indicates that the first meeting was 72.49% and experienced a significant increase in the second meeting to 85.08 and the third meeting to 86.11 so that the average percentage of student learning activity observations in implementation project-based learning with Canva obtained a result of 81.22% in the active category. So, it can be concluded that students’ activity in using project-based learning with Canva at SMAN 11 Pinrang was increased.